NOMADERS FREMTIDSUDSIGTER: Beduiner i oliestaterne Qatar og Bahrain og pashtuner i Afghanistan - Ferdinand, Klaus (Tidsskriftet Antropologi, 1998)
Klaus Ferdinand: Nomads’ Perspectives on the Future. Beduins in the Oil States Qatar and Bahrain and Pashtuns in Afghanistan The study of pastoral nomads and especially the processes of change they are (and have been) undergoing has, for several decades. been an important field of study in anthropology. In the Middle East nomadism does not only comprise pastoral nomads but a wide variety of other developments in interplay with the surrounding social environment. This “multi-resource nomadism” (Salzman 1969) or “extended nomadism” is culturally stamped by its local or regional cultural and social surroundings. In Afghanistan these developments have resulted in settling down. When does it become appropriate to stop talking of nomadism and nomads altogether? This is discussed on the background of material from the Arab Gulf States Qatar and Bahrain and from Afghanistan. Furthermore, the very different status of the nomads in Arabia and in Afghanistan (and Iran) is discussed. In Arabia traditional Beduin life is fast disappearing, but it is kept “alive” in a new role as part of the affluent oil states’ national identity and exhibited in their museums and centres of national heritage. In Afghanistan the situation is quite the reverse: here the nomads have generally been considered “wild” and represented an outdated form of life. In spite of this faet, however, they continue to exist, and to all appearances are also expanding in numbers throughout the 1980s and 1990s with the turbulent and chaotic war situation. Nevertheless, as nomadism is on its way out and becoming a matter of history, it is argued that our studies also have to become historical, and once again also have to comprise the study of material culture. This is so, because our rich museum collections in the future will serve as primary data collections. This necessitates having them well doeumented and this is not usually the case!